Recombinant long‐acting glycoPEGylated factor IX (nonacog beta pegol) in haemophilia B: assessment of target joints in multinational phase 3 clinical trials. (3rd March 2016) - Negrier, C.; Young, G.; Abdul Karim, F.; Collins, P. W.; Hanabusa, H.; Colberg, T.; Goldman, B.; Walsh, C. E.; ,
Abstract : Background: The paradigm ™ 2 and 4 phase 3 clinical trials investigated the safety and efficacy of nonacog beta pegol, a recombinant glycoPEGylated factor IX (FIX) with extended half‐life, in previously treated haemophilia B patients. Aim: These post hoc analyses investigated the bleeding patterns in target joints. Methods: Patients randomized to 40 or 10 IU kg −1 once weekly prophylaxis who had at least one target joint were included. Baseline demographics and disease‐specific data were collected. Bleeding patterns were assessed, and an International Society on Thrombosis and Haemostasis (ISTH) definition of target joints was used. Results: A total of 67% and 8% of patients in the 40 and 10 IU kg −1 arm, respectively, did not experience target joint bleeds during the paradigm ™ 2 trial. Twenty‐four target joints were recorded in each prophylaxis arm at baseline. During the paradigm ™ 2 trial, no bleeds were reported in 17 (71%) and 7 (29%) target joints in the 40 and 10 IU kg −1 arms respectively. All target joint bleeds in the 40 IU kg −1 once weekly prophylaxis arm were controlled with a single injection of 40 IU kg −1 nonacog beta pegol. By the latest ISTH definition, 90% and 58% of target joints in the 40 and 10 IU kg −1 arms, respectively, were no longer considered target joints at the end of the paradigm ™ 2 trial. At the end of the paradigm ™ 4 extension trial, all target joints in the 40 IU kg −1 arm were no longer considered target joints. Conclusion: Routine prophylaxis with 40 IU kg −1 once weekly nonacog beta pegol has the potential for effective management of target joint bleeds in haemophilia B patients.